2018
DOI: 10.1080/0142159x.2018.1439579
|View full text |Cite
|
Sign up to set email alerts
|

The development of a pragmatic, clinically driven ultrasound curriculum in a UK medical school

Abstract: Whether ultrasound (US) should be incorporated into a medical undergraduate curriculum remains a matter of debate within the medical education arena. There are clear potential benefits to its early introduction particularly with respect to the study of living anatomy and physiology in addition to the learning of clinical skills and procedures required for the graduate clinical practice. However, this needs to be balanced against what is perceived as an added value in addition to financial and time constraints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 36 publications
2
43
0
1
Order By: Relevance
“…This observation emphasizes the fact that experience and hands‐on practice are required beyond didactic instruction to optimize the accuracy of the readings and the interpretation of musculoskeletal US images. This and other observations support the belief that point‐of‐care (musculoskeletal) US imaging can be learned and correctly applied by nonradiologists but requires appropriate education, continued practice, and accumulation of experience to ensure accurate clinical assessments …”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This observation emphasizes the fact that experience and hands‐on practice are required beyond didactic instruction to optimize the accuracy of the readings and the interpretation of musculoskeletal US images. This and other observations support the belief that point‐of‐care (musculoskeletal) US imaging can be learned and correctly applied by nonradiologists but requires appropriate education, continued practice, and accumulation of experience to ensure accurate clinical assessments …”
Section: Discussionsupporting
confidence: 65%
“…This and other observations support the belief that point-of-care (musculoskeletal) US imaging can be learned and correctly applied by nonradiologists but requires appropriate education, continued practice, and accumulation of experience to ensure accurate clinical assessments. [49][50][51][52][53] A final step was the establishment of interoperator reliability, which examined the extent of agreement of image interpretation between providers when acquiring images independently. The operators were experienced in musculoskeletal US and acquired the images from patients with hemophilia during a 1-day workshop.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that these devices will become commonly used over time, so we believe that it is important that future clinicians are trained appropriately. Although ultrasound has been integrated well into undergraduate medical education in the USA, this cannot be said for the UK, with few medical schools integrating longitudinal ultrasound education into the curriculum here . Furthermore, the use of HHU may lead to significant savings to the health system, when used appropriately …”
Section: The Why and The What For …mentioning
confidence: 99%
“…Although ultrasound has been integrated well into undergraduate medical education in the USA, 2 this cannot be said for the UK, with few medical schools integrating longitudinal ultrasound education into the curriculum here. 2 Furthermore, the use of HHU may lead to significant savings to the health system, when used appropriately. 3…”
mentioning
confidence: 99%
“…With growing student interest in cardiac ultrasound examination [8], multiple studies have demonstrated feasibility and bene ts of integrating cardiac POCUS into the undergraduate medical education (UME) curriculum [9][10][11][12][13][14]. A comprehensive review article on cardiac POCUS in medical school education described that 12 medical schools in the United States, Canada, Norway, United Kingdom, Israel, Poland, and China have incorporated cardiac POCUS curricula [15].…”
Section: Introductionmentioning
confidence: 99%